2016
DOI: 10.1109/twc.2016.2547912
|View full text |Cite
|
Sign up to set email alerts
|

Area Spectral Efficiency Analysis and Energy Consumption Minimization in Multi-Antenna Poisson Distributed Networks

Abstract: This paper aims at answering two fundamental questions: how area spectral efficiency (ASE) behaves with different system parameters; how to design an energy-efficient network. Based on stochastic geometry, we obtain the expression and a tight lower-bound for ASE of Poisson distributed networks considering multi-user MIMO (MU-MIMO) transmission. With the help of the lower-bound, some interesting results are observed. These results are validated via numerical results for the original expression. We find that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 27 publications
2
28
0
1
Order By: Relevance
“…Moreover, the impact of interference-driven correlation on receiver arrays in ad-hoc network as well as the downlink of a single-tier cellular network was investigated in [49] and [50]. The authors of [51], [52], [53] demonstrated the importance of theoretical results developed in [7], [40], [42] for the optimization of MIMO ellular systems. For instance, in [52], the coverage probability, spectral efficiency, and load balancing in MIMO systems were considered.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the impact of interference-driven correlation on receiver arrays in ad-hoc network as well as the downlink of a single-tier cellular network was investigated in [49] and [50]. The authors of [51], [52], [53] demonstrated the importance of theoretical results developed in [7], [40], [42] for the optimization of MIMO ellular systems. For instance, in [52], the coverage probability, spectral efficiency, and load balancing in MIMO systems were considered.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, in [52], the coverage probability, spectral efficiency, and load balancing in MIMO systems were considered. Further, [51] optimized ASE and energyefficiency in uplink/downlink multi-user MIMO system. For managing inter-cell interference, [54] investigated the coupled optimized offloading and coordinated MIMO communications.…”
Section: Related Workmentioning
confidence: 99%
“…Further, concerning CoMP among BSs, the coverage probabilities for a typical UE in heterogeneous downlink networks was studied in [11], [12], and the signal-to-interference ratio (SIR) meta distribution for both the general UE and the worst-case UE under the Poisson multiple-tier cellular networks was analyzed in [13]. Most recently, stochastic geometry was integrated with optimization theory for optimal design and performance analysis of cellular networks, see e.g., [14]- [17].…”
Section: Introductionmentioning
confidence: 99%
“…With the dense deployment of BSs in HCN, more and more attention has been paid to the energy efficiency (EE) of HCN [21][22][23][24]. In [25][26][27][28][29], the EE of HCN under the PPP model is studied, and the strategies to optimize the EE are proposed from the aspects of transmit power, BS sleeping, BS density and so on.…”
Section: Introductionmentioning
confidence: 99%